Therapeutic Role of MSC-Secretome in Type 2 Diabetic Models: Correlation between Improved HOMA-IR and Attenuated Pancreatic-Hepatic Structural Alterations - Wulandari, Putri Karenina Amalia; Sari, Fikriya Novita; Ardianto, Okky; Widyatmoko, Agus (International Journal of Cell and Biomedical Science, 2025)
Background: Type 2 diabetes mellitus (T2DM) is characterized by insulin resistance, β-cell dysfunction, and chronic hyperglycemia leading to multiorgan complications. Conventional therapies primarily target glycemic control but often fail to prevent progressive pancreatic and hepatic injury. This study investigated the therapeutic potential of hypoxic mesenchymal stem cell (MSC) secretome in improving insulin resistance and restoring tissue integrity in T2DM rat models. Methods: Male Wistar rats were induced with T2DM using a high-fat diet followed by streptozotocin–nicotinamide administration and subsequently treated intraperitoneally with MSC-secretome for four weeks. Fasting blood glucose, serum insulin levels, and HOMA-IR index were assessed, followed by histopathological evaluation of hepatic and pancreatic tissues. Results: The results showed that T2DM was significantly associated with elevated insulin levels and HOMA-IR values compared to the normal group, confirming insulin resistance. Treatment with MSC-secretome markedly reduced both parameters (p < 0.001), suggesting improved insulin sensitivity. Histological analyses revealed substantial hepatic and pancreatic degeneration in untreated diabetic rats, characterized by hepatocellular vacuolization, steatosis, and islet necrosis. Conclusion: Conversely, MSC-secretome treatment demonstrated remarkable restoration of lobular architecture, reduced lipid accumulation, and regeneration of pancreatic islets. These reparative effects are attributed to the secretome’s bioactive components that regulate oxidative stress, inflammation, and cellular regeneration. In conclusion, hypoxic MSC-secretome administration effectively ameliorates insulin resistance and attenuates hepatic and pancreatic damage in T2DM rats, underscoring its potential as a novel non-cell-based therapeutic strategy for metabolic disorders.